MORPHOLOGICAL CHARACTERISTICS OF TWELVE FINGER ULCER DISEASE (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
Metabolic syndrome is a chronic and acute metabolic disorder in the human body, and recently there has been a lot of talk about metabolic syndrome (MS). Why is this cash register dangerous? Because it can lead to the development of many serious diseases, such as atherosclerosis, heart attack, stroke, kidney failure, cancer, and the most common is diabetes.